Pembelajaran Agama Islam di Yayasan Lembaga Kesejahteraan Sosial Lanjut Usia Perwira Purbalingga - Agam An’amta Hanuwijaya; Makhful Makhful (UM Purwokerto Press, 2023)
Islamic religious education certainly cannot be separated from the life process of all humans and will continue from birth to old age. Humans from birth will continue to experience development, both psychologically and physically. The potential is to continue to develop because humans are living beings who have a reason. The dynamic side is the nature of human development, meaning that changes will continue to be made by humans. Education is one of human development. This study aimed to determine Islamic religious learning at the Purbalingga Senior Officers' Social Welfare Foundation. The type and approach of the research are field research and the type of qualitative research. The research subjects were caretakers and assistants for the elderly. The data analysis technique used primary data from interviews, observations, and documentation. The data collected will be analyzed qualitatively using descriptive methods. The results of research and discussions conducted by researchers regarding Islamic religious learning at the Perwira Purbalingga Elderly Social Welfare Foundation indicate that the Islamic spiritual guidance program is Islamic religious learning using direct methods, lectures, and memorizing the Qur'an juz 30 (short letters). The Islamic learning model using the Islamic spiritual guidance method that has been applied requires elderly companions to have not only master religious knowledge but also social problems faced by the elderly. A direct approach between the companion and the elderly during the Islamic spiritual guidance program, so that the problems faced by each elderly can be controlled properly.